The function, f(x) = –2x2 + x + 5, is in standard form. The quadratic equation is 0 = –2x2 + x + 5, where a = –2, b = 1, and c = 5. The discriminate b2 – 4ac is 41. Now, complete step 5 to solve for the zeros of the quadratic function. 5. Solve using the quadratic formula. x = What are the zeros of the function f(x) = x + 5 – 2x2? x = x = x = x =

Respuesta :

Answer:

A quadratic equation [tex]ax^2+bx+c=0[/tex]   ....[1] where, a, b and c are coefficient then;

the solution fore this equation we have;

[tex]x = \frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]         ....[2]

Given the function in the standard form:

[tex]f(x) = -2x^2+x+5[/tex]

The quadratic equation is:

[tex]0 = -2x^2+x+5[/tex]

On comparing with equation [1] we have;

a = -2 , b = 1 and c = 5.

The discriminant is given by:

[tex]\text{Discriminant} = b^2-4ac[/tex]

then;

[tex]\text{Discriminant} = (1)^2-4(-2)(5) = 1+40 = 41[/tex]

Solve for the zeros of the quadratic function:

Substitute the given values in [1] we have;

[tex]x = \frac{-1 \pm \sqrt{41}}{2(-2)} = \frac{-1 \pm \sqrt{41}}{-4}[/tex]

then;

[tex]x = \frac{-1 + \sqrt{41}}{-4}[/tex] and [tex]x = \frac{-1 - \sqrt{41}}{-4}[/tex]

⇒[tex]x = \frac{1 - \sqrt{41}}{4}[/tex] and [tex]x = \frac{1 + \sqrt{41}}{4}[/tex]

Therefore, the zeros of the given  function are:

[tex]x = \frac{1 - \sqrt{41}}{4}[/tex] , [tex]\frac{1 + \sqrt{41}}{4}[/tex]

Using quadratic function concepts, it is found that the zeros are:

  • [tex]x = \frac{1 - \sqrt{41}}{4}[/tex]
  • [tex]x = \frac{1 + \sqrt{41}}{4}[/tex]

What is a quadratic function?

A quadratic function is given according to the following rule:

[tex]y = ax^2 + bx + c[/tex]

The discriminant is:

[tex]\Delta = b^2 - 4ac[/tex]

The solutions are:

[tex]x_1 = \frac{-b + \sqrt{\Delta}}{2a}[/tex]

[tex]x_2 = \frac{-b - \sqrt{\Delta}}{2a}[/tex]

In this problem, the function is:

[tex]f(x) = -2x^2 + x + 5[/tex]

Hence the discriminant is:

[tex]\Delta = b^2 - 4ac = 1^2 - 4(-2)(5) = 41[/tex]

Then, the zeros are:

[tex]x_1 = \frac{-1 + \sqrt{41}}{2(-2)} = \frac{1 - \sqrt{41}}{4}[/tex]

[tex]x_2 = \frac{-1 - \sqrt{41}}{2(-2)} = \frac{1 + \sqrt{41}}{4}[/tex]

You can learn more about quadratic function concepts at https://brainly.com/question/24737967